2018
DOI: 10.1007/s00330-018-5473-4
|View full text |Cite
|
Sign up to set email alerts
|

Can digital breast tomosynthesis perform better than standard digital mammography work-up in breast cancer assessment clinic?

Abstract: • Use of DBT in the assessment clinic results in increased diagnostic accuracy. • Use of DBT in the assessment clinic improves performance of radiologists and also increases the confidence in their decisions. • DBT may reduce the need for additional views, ultrasound imaging, and biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…1 ). Finally, 20 articles with 44513 patients and 58388 lesions fulfilled the eligibility criteria [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ]. Table 1 presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Finally, 20 articles with 44513 patients and 58388 lesions fulfilled the eligibility criteria [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ]. Table 1 presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 50% were conducted in Asian countries [ 18 19 20 23 25 27 29 31 32 33 ], and there were four prospective studies [ 18 19 32 33 ]. Five studies had patients with breast density ≥ 2 or b according to American College of Radiology (ACR) [ 28 29 30 31 34 ], nine studies consecutively sampled participants [ 18 21 22 24 25 26 32 34 35 ], and 13 studies performed a per-lesion analysis [ 18 19 20 21 22 23 25 26 28 29 31 32 33 34 ]. Five studies included lesions without calcifications [ 26 28 29 30 34 ], and three studies symptomatic patients only [ 19 29 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results showed no improvement in observer performance with the addition of DBT. Later studies concluded that observer performance increases with the addition of DBT to DM when using more advanced Hologic models 13,16,3543. Specifically in the detection and characterization of invasive lobular cancers, DM&DBT significantly increases sensitivity compared to DM alone 44…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 99%
“…A lot of review work has been completed on the use of DBT in breast cancer screening 8,12,13. However, to the best of our knowledge, no review work has summarised clinical observer studies separately for each of the four common methods with which DBT can be implemented in screening: (2-view) DBT alone [DBT or 2vDBT],(2-view) DBT with (2-view) DM [DM&DBT],Single-view DBT [1vDBT] with or without single or double view DM [1vDM or 2vDM],(2-view) DBT with (2-view) SM [DBT&SM].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study by Greenberg et al (26), 46 of 131 patients who underwent DBT (35.1%) had no additional mammographic views performed at recall (compared with 12 of 190 [6.3%] in the FFDM-only group), suggesting a more efficient recall assessment (P , .001). In the Tomosynthesis Assessment Clinic Trial (75), which involved 144 women, the use of DBT was associated with a significant reduction in the need for additional views (x 2 DBT plus SM (79), the estimated average glandular dose for a single mammographic view (6standard deviation) was 1.58 mGy 6 0.61 (range, 0.74-4.51 mGy) for FFDM and 1.95 mGy 6 0.58 (range, 1.05-3.78 mGy) for DBT. By replacing FFDM with SM in the DBT plus FFDM examination, the average glandular dose was decreased by approximately 45%, with the dose with DBT plus SM just 19% higher than that with FFDM alone (49).…”
Section: Practice Considerationsmentioning
confidence: 99%